An industrial application of the lean and agile model for product development: a manufacturing case study - Fargher, Glyn P.; Aboudaber, Marwan; Bruneau, Thomas; Pandjawatchou, Jordan; Reynaud, Julie; Regnier, Marie; Khan, Muhammad; Al-Ashaab, Ahmed (Sage, 2026)
Manufacturing organisations face pressure to develop effective engineering solutions while maintaining their competitiveness in rapidly evolving markets. This challenge necessitates product development approaches that balance rigorous knowledge-driven methodswith responsive adaptation to changing requirements. This research presents an empirical application of the Lean and Agile Model for Product Development (LAMPD) in a manufacturing environment, addressing critical gaps in integrated methodologies for hardware contexts. LAMPD was implemented through a 4-month case study at Atlas Copco Henrob, a UK manufacturer of self-piercing riveting systems, focusing on enhancing a rivet feeder system used in automotive manufacturing that had not previously undergone dedicated design optimisation. The research aimed to document LAMPD implementation processes, determine its impact on design efficiency, identify process benefits and challenges, and explore implications for manufacturing product development practices. The LAMPD framework systematically integrated Set-Based Concurrent Engineering principles with Agile methodologies including Scrum ceremonies and Kanban visualisation techniques across three development phases: Project Definition, Project Feasibility, and Project Realisation. The integrated approach facilitated evidence-based decision-making, which resulted in a 53% component reduction, eliminated two sensors from the original design, and improved system reliability by reducing false readings from 12% to near zero principally through the rigorous application of SBCE methodology combined with continuous integration cycles. Challenges identified included harmonising sprint cadences with traditional phase boundaries and balancing multiple methodological frameworks without compromising their individual strengths. Despite these implementation complexities, the research demonstrates that combining Lean knowledge management principles with Agile responsiveness creates substantial value in manufacturing product development. The LAMPD model provides organisations with practical mechanisms to enhance both design efficiency and process adaptability, contributing to theory and practice by showing how integrated approaches can significantly improve product development outcomes in hardware manufacturing contexts.
Keywords: 40 Engineering; 4010 Engineering Practice and Education; Generic health relevance; 9 Industry, Innovation and Infrastructure; Design Practice & Management; 4014 Manufacturing engineering; set-based concurrent engineering; methodology integration; hardware development; manufacturing case study; lean product development; agile product development; Scrum; Kanban; stage-gate process